Alterations of gut microbial pathways and virulence factors in hemodialysis patients - Shi, Xiaochun; Gao, Bei; Srivastava, Anvesha; Izzi, Zahra; Abdalla, Yoosif; Shen, Weishou; Raj, Dominic (Frontiers in Cellular and Infection Microbiology, 2022)
Alterations in gut microbiota might contribute to uremic toxicity and immune dysregulation in patients with end-stage renal disease. Hemodialysis patients are prone to infection and higher mortality following sepsis. The virulence factors in the gut metagenome have not been well studied in hemodialysis patients, which could be employed by microorganisms to successfully thrive and flourish in their hosts. In this study, we performed shotgun metagenomics sequencing on fecal DNA collected from 16 control subjects and 24 hemodialysis patients. Our analysis shows that a number of microbial species, metabolic pathways, antibiotic resistance and virulence factors were significantly altered in hemodialysis patients compared with controls. Especially, erythromycin resistance methylase, pyridoxamine 5-phosphate oxidase, and streptothricine-acetyl-transferase were significantly increased in hemodialysis patients. The findings in our study laid a valuable foundation to further elucidate the causative role of virulence factors in predisposing HD patients to infection and to develop treatment strategies to reduce the genetic capacities of antibiotic resistance and virulence factors in HD patients.